Study on soil quality effect of reconstructing by Pisha sandstone and sand soil - Zhang Haiou; Guo Zhen; Zhou Hang; Yang Chenxi; Wang Yingguo (Open Geosciences, 2023)
In order to explore the effect of reconstructing soil quality change after adding Pisha sandstone rich in clay mineral materials to improve sandy soil in the Mu Us Sandy Land. Long-term field monitoring experiments were conducted to study the characteristic changes of the reconstructed soil carbon and nitrogen content and corn yield with different proportions of Pisha sandstone and sand. The results showed that after 9 years of experiment, compared with the original sandy soil, in T1, T2, and T3 treatments the reconstructed soil organic matter content increased by 10, 12, and 11 times, total nitrogen content increased by 5.5, 5.4, and 3.9 times, and corn yield increased by 43.9, 105.9, and 58.5%. Especially, the corn yield of T2 and T3 treatment is greater than or equal to the corn yield of local high-yield fields. In summary, the reconstructed soil quality in different proportions has developed toward a good trend after long-term planting. T2 and T3 treatments have the best effects on reconstructing soil carbon and nitrogen accumulation reconstruction and corn yield increase. T2 and T3 treatments are recommended as the best scientific ratio for improving sandy soil with Pisha sandstone in Mu Us Sandy Land. This method has important reference and guidance for ecological remediation of desertification and degraded land.